Circulating gamma-glutamyl transpeptidase, systemic inflammation biomarkers and risk of lung cancer in the UK biobank prospective cohort study - Ting Chen; Jian Ma; Qing Zhou; Lilong Pang; Lingling Song; Xinwei Zuo; Yangjiao Bai; Xuemei Lian (Scientific Reports)
Abstract Epidemiological evidence on the association between Gamma-glutamyl transpeptidase (GGT) and lung cancer risk is limited. Meanwhile, whether inflammation can modify the association of GGT-lung cancer remains unknown. We assessed the relationship of GGT-lung cancer and modification effects of inflammation biomarkers in 412,634 participants from UK Biobank using Cox models and interactive analysis. This study founds participants in the top quartile of GGT level had an increased risk of lung cancer by 45.1% (HR, 1.451; 95% CI, 1.299–1.621; p < 0.001) compared to those in the bottom quartile. Positive associations were also observed between inflammation biomarkers (lymphocyte, neutrophil, platelet, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, systemic immune-inflammation index, white blood cell [WBC], C-reactive protein [CRP]) and lung cancer risk. Meanwhile, we observed the WBC and CRP served varying modification effects on the GGT-lung cancer associations (p interaction <0.01). As WBC level increased, the HR of GGT for lung cancer tended to increase and then decrease. However, with an increase in CRP, the HR for GGT-lung cancer significantly declined. Circulating GGT is positively associated with lung cancer. Inflammation biomarkers have mixed modification effects on the association between GGT and lung cancer. Attention should be paid to the prediction of lung cancer by WBC and CRP combined with GGT.